DNAase I sensitivity of genes expressed during myogenesis. - Carmon, Y (1982)
Cultures of a rat myogenic cell line were used to examine the question of whether in proliferating precursor cells genes which are programmed to be expressed later in development, in the same cell lineage, differ in DNAase I sensitivity from genes which are never expressed in these cells. Nuclei isolated from proliferating mononucleated myoblasts, differentiated cultures containing multinucleaged fibers, and rat brain, were treated with DNAase I. The sensitivity of the genes coding for the muscle-specific alpha-actin, myosin light chain 2 and the nonmuscle beta-actin was measured by blot hybridization of nuclear DNA with the corresponding cloned cDNA and genomic DNA probes. The sensitivity of these genes was compared to that of a gene not expressed in the muscle tissue. The results showed that in the muscle precursor cells, the potentiality of tissue-specific genes to be expressed is not reflected in DNAase I sensitivity. The changes which render these genes preferentially sensitive to DNAase I take place during the transition to terminal differentiation. The results showed also that the region of DNAase I sensitivity of the alpha-actin gene in the differentiated cells ends between 40 to 700 bp 5' to the structural gene. No DNAase I hypersensitive site was detected 5' to the alpha-actin gene.